Hasnul Jamal Saidon projection artworks: Semiotic analysis on veil of an artist and a fictional dialogue - Hannah Kong Nyuk Fun; Imelda Ann Achin; Addley Bromeo Bianus (Akademi Seni dan Teknologi Kreatif, UMS, 2021)
New media art acts as an important instrument for bridging the gap between art communication and society. The situation in our country regarding this new media development is deficient in terms of intellectualism qualities of studies and comprehension of projection art. The purpose of this research is to study projection art in Malaysia in order to ascertain how artists use technology and visual art semiotics to facilitate the effective transmission of messages to audiences. This paper discusses the projection artworks produced by Hasnul Jamal Saidon titled Veil of an Artist and A Fictional Dialogue. Semiotics approaches is used to analyse the projection artwork of Hasnul Jamal Saidon which include construct the content analysis semiology and in-depth interviews serving as key data collecting components. This research also aims to discover the value of the message conveyed by Hasnul's projection artworks as well as to decipher the signs and meanings included in each piece of art. According to the study, Hasnul's projection artwork exemplifies new media and its constantly changing, complicated ways in which individuals express and interpret the value of the subject, views, and ideologies of nature, as well as social, moral, and traditional ideals. The results of the study revealed that the artworks may successfully convey the artist's intended meaning, as well as the themes and issues on which they addressed, regardless of the time period or location in which it was produced.